Analysis of the Behavioral Patterns of the Flower Python (Malayopython Retikulatus) at the Indonesian Sioux Snake Foundation - Hasna Maulia (Formosa Journal of Applied Sciences, 2023)
Reptiles (creeping animals, Latin "reptans" meaning "crawling" or "crawling") are a group of cold-blooded vertebrates whose bodies are covered with scales. Reptiles are quadrupeds (four-legged animals) that lay eggs, the embryos of which are covered with amniotic membranes. Most reptiles are oviparous (lay eggs), but some squamate species are viviparous (give birth). Living reptiles feed their fetuses with a type of placenta similar to that of mammals. The size of reptiles varies from 1.6 cm (small gecko, Sphaerodactylus ariasae) to 6 m high and weighing 1 ton (salt water crocodile, Crocodylus porosus). The field of natural science that studies reptiles is herpetology.